A Comparison of Mental Imagery and Physical Practice on Dynamic Balance in Patients with Multiple Sclerosis - Mehrzad Kharestani; Mahdi Zarghami; Parvaneh Shafiniya (University of Tehran, 2016)
The aim of this study was to investigate the effect of mental imagery and physical practice on dynamic balance in male patients with multiple sclerosis. This study was semi-experimental and the statistical population included male patients with multiple sclerosis in Ahvaz city in 2012 (N=300). For sampling, Visual and Kinesthetic Imagery Questionnaire and EDSS scale were used. Finally, 33 patients with similar ability of imagery and moderate disorder in EDSS Scale were selected and randomly assigned to 3 groups: mental imagery-physical practice (n=11), mental imagery (n=11) and physical practice (as control group, n=11). The TUG test was used to assess dynamic balance in the pretest, posttest and retention test. The training protocol consisted of 3 sessions a week for 6 weeks. Posttest was performed 2 weeks after the last session of the training protocol. After investigating the data normality and variance equality, data were analyzed using one-way analysis of variance with repeated measures, one-way analysis of variance and Tukey post hoc test. The results indicated a significant difference in posttest (P=0.02) and retention (P=0.003) phases among the groups, and combined group had a better performance than the other groups during both phases. According to these results, mental imagery can be used as a practical method for the better performance of dynamic balance in patients with multiple sclerosis.